2011
DOI: 10.4161/trns.2.3.15829
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal myogenesis andMyf5activation

Abstract: Myogenic regulatory factors (MRFs) are the master regulators of skeletal myogenesis. Among the MRFs, Myf5 is the earliest to be expressed and is regulated by a complex set of enhancers. The expression of Myf5 defines different muscle populations in the somite. Furthermore, Myf5 expression is also found in non-muscle tissues, such as preadipocytes and neurons. Here, we present a current view on the regulation of skeletal myogenesis by transcription factors and cellular signals, with an emphasis on the complexit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 76 publications
2
79
0
1
Order By: Relevance
“…Myf5 is the first MRF to be expressed, which marks the commitment of progenitor cells into skeletal muscle lineage [2]. We found that similar to Pax3, Myf5 transcripts were also detected by day 4 of differentiation (Figure 4A).…”
Section: Resultsmentioning
confidence: 70%
“…Myf5 is the first MRF to be expressed, which marks the commitment of progenitor cells into skeletal muscle lineage [2]. We found that similar to Pax3, Myf5 transcripts were also detected by day 4 of differentiation (Figure 4A).…”
Section: Resultsmentioning
confidence: 70%
“…Sequential expression of the myogenic regulatory factors such as Myf5, MyoD, and myogenin, is essential for spatiotemporal expression of muscle specific genes, which is controlled by progressive activation of complex cis -regulatory elements13.…”
mentioning
confidence: 99%
“…These transcription factors are essential for the determination and differentiation of skeletal muscle during embryogenesis (18, 45), and display the unique ability to convert non-muscle cell types to skeletal muscle (58). Myf5 is the first MRF to be expressed, at E8 in the mouse (42).…”
Section: Introductionmentioning
confidence: 99%